Plasma Signatures of Lipid and Cellular Energy Metabolism in the 5xFAD Mouse. (20th December 2022) - Gross, Thomas J; Vu, Michael M; Malhas, Rond; Green, Kim N; MacGregor, Grant R; Tenner, Andrea J; LaFerla, Frank; Mapstone, Mark
Abstract: Background: Identifying early biomarkers of Alzheimer's disease (AD) could help us understand mechanisms of AD and provide opportunities to develop novel therapeutics. The plasma metabolome is a rich source of potential biomarkers. Our goal is to analyze metabolomics in new models of AD being developed by MODEL‐AD. Here, we examine lipid and cellular energy metabolism via plasma metabolomics in the 5xFAD mouse. Method: We examined age‐dependent changes in the abundance of plasma metabolites obtained from 10 (5M, 5F) 5xFAD and 10 (5M, 5F) wild type (WT) mice at 4‐, 12‐, and 18‐months. Blood was collected at time of death and the plasma fraction was analyzed using liquid chromatography mass spectrometry (LC‐MS). We measured 762 lipids and 204 polar metabolites. We used Metaboanalyst 5.0 for all analyses. Result: We found increased abundance of acylcarnitines in 5xFAD mice relative to WT mice at 4‐months of age ( q < 0.05) which reversed by 18 months of age where there was a relative depletion of acylcarnitines in the 5xFAD mice ( q < 0.05). The best 10 discriminant features from Component 1 of a sPLS‐DA were acylcarnitines (4/10) and lipids (4/10) at 4‐months, lipids (8/10) at 12‐months, and acylcarnitines (6/10) at 18‐months. Using these 10 features, ROC area under the curve (AUC's) was 0.95 (95%CI 0.78‐1.0) at 4‐months, 0.91 (95%CI 0.61‐1.0) at 12‐months, and 1.0 (95%CI 1.0‐1.0) at 18‐months. We examined changes in multivariate lipid and metabolite patterns between the two groups over time. We found 30 metabolites with significant interactions between Time and Group. Pathway analysis using these 30 metabolites showed enrichment for Glycerophospholipid Metabolism ( q < 0.05) indicating the 5xFAD mice show more rapid depletion of these particular lipids over time. Conclusion: We see changes in cellular energy and lipid metabolism in aging 5xFAD mice. These changes in energy metabolism may reflect an early compensatory shift as amyloid plaques appear which then fails as the plaques establish and the animal ages. We also find significant time‐dependent changes in lipid and metabolite abundances especially metabolites associated with glycerophospholipid metabolism. These age‐dependent changes in lipid and metabolomic profiles of the 5xFAD relative to WT suggest a dynamic and complex metabolic milieu.